Comportamiento del empleo en empresas privadas formales de diez a más trabajadores en la región Loreto periodo 2014 – 2018 - Romero Collantes, Rosita Milagritos (2021)
The study design was descriptive in scope, with a quantitative, non-experimental and longitudinal approach. The sample was made up of the statistical records of the employment rate of formal private companies in the Loreto region, with ten or more workers from different economic activities between the years 2014 to 2018. The objective was to analyze the growth rate, and also established how specific objectives, analyze the employment growth rate for each economic activity and recognize which economic activity had the highest growth rate. The study concludes that in Loreto there was no growth in the labor index in any of the five economic activities analyzed in the study period: primary activity, manufacturing, commerce, transportation and communications and services, contrary to the hypothesis raised in the research. Only the commerce sector remained above one hundred percent compared to the previous years of the study